Increasing Student Grades in the Process of Returning West Irian Through the Community Learning Approach to Student in Class IX.1 MTsN 4 Pasaman - Rayeni (Yayasan Citra Dharma Cindekia, 2022)
This Classroom Action Research is the application of the cooperative learning model (group-based) applied in the classroom which is motivated by the difficulties of students in the process of grazing in West Irian. The purpose of this learning improvement action is to improve the ability of students in the process of returning the West Irian to class IX.1 students with Competency Standards (SK) Understanding Efforts to Defend the Republic of Indonesia. The results , the implementation of cycle 1 in the classroom shows that by applying/using. Group-based learning model obtained an average score of 73.68 students. In cycle 2 the average score of students rose to 77.39. With the scientific learning model based on groups, it turns out that it can increase students' abilities in the material for the return process of West Irian. This competence can be seen from the first indicator , students are happy and active in learning activities. Second , the increasing ability of students in the process of returning west Irian. Thus in the learning process students are able to build their own concepts about learning materials from the results of group learning activities, not the results of the presentation from the teacher. The teacher's role is only as a guide . This learning model is recommended to MTsN teachers as an alternative to improve students' abilities in the process of shepherding West Irian. So, it can be concluded that from the implementation of the activities in cycle 1 and cycle 2, there was an increase in the grades of class IX.1 MTsN Bo 4 Pasaman on the subject of Returning West Irian